Adjuvant breast radiotherapy, endocrine therapy, or both after breast conserving surgery in older women with low-risk breast cancer: Results from a population-based study. (January 2021) - Joseph, Kurian; Zebak, Sarah; Alba, Veronica; Mah, Kayla; Au, Cara; Vos, Larissa; Ghosh, Sunita; Abraham, Aswin; Chafe, Susan; Wiebe, Ericka; Liu, Hong-Wei; Chambers, Carole; et al.
Highlights: Adjuvant radiotherapy alone is a viable alternative to endocrine therapy alone in older women with low risk EBC. No difference in recurrence-free survival or breast cancer specific survival between radiotherapy or endocrine therapy. Comorbidity in older patinets was independently associated with reduced overall survival. Abstract: Background and Purpose: The relative benefit of adjuvant radiotherapy (RT) alone in older women with low-risk early breast cancer (EBC) remains unclear. It is hypothesized that adjuvant RT-alone can improve outcomes of older patients with low-risk EBC, similar to endocrine therapy (ET) alone or combination of RT + ET. Methods: In this population based study, we identified all women aged ≥70 with T1–2, N0, ER+ve, Her-2/neu−ve EBC treated with breast conserving surgery (BCS), followed by adjuvant treatments (RT-alone, ET-alone, or RT + ET combination) from 2005 to 2015. Primary outcome measures were recurrence-free survival (RFS), overall survival (OS), and breast cancer specific survival (BCSS). Treatment details were collected and Charlson Comorbidity Index (CCI) was calculated. Results: A total of 1166 patients were identified. Median follow-up was 76.5 months. Adjuvant treatments: BCS only 130 (11%), RT 378 (32.5%), ET 161 (14%), and RT + ET 497 (42.5%). Less than 60% of women completed 5-years of ET. Compared to BCS alone, RT resulted in significant improvement in RFS (HR = 0.174; p  < 0.001), similar to ET (HR = 0.414; p  = 0.007) and RT + ET (HR = 0.236; p  < 0.001). Determinants of OS were age, tumor grade, comorbidities, and adjuvant therapy. Increased comorbidity scores (0 vs. 1; 0 vs. ≥2) were associated with reduced OS (HR = 1.40; p  = 0.013 and HR = 1.98; p  < 0.001), without impact on RFS or BCSS. Conclusions: Adjuvant RT-alone is a reasonable alternative to ET or RT + ET for older women with biologically favorable EBC. No difference in RFS or BCSS was noted between RT, ET, and RT + ET. Comorbidity was independently associated with reduced overall survival.